KETEPATAN PEMBERIAN OPINI AUDIT OLEH AKUNTAN PUBLIK DAN FAKTOR-FAKTOR YANG MEMPENGARUHI: STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI BANTEN - Dirvi Surya Abbas; Basuki Basuki (COMPETITIVE, 2020)
This study aims to explain the influence of Independence, Audit Skills, Accounting Knowledge and Auditors' and Skepticism on the Accuracy of Audit Opinion. This research uses purposive sampling and accidental sampling techniques. After distributing the questionnaire, a sample of 30 auditors who were respondents were taken from a public accounting firm located in Banten province. Hypothesis testing in this study was carried out using multiple linear regression analysis.In the results of this study revealed that the variable independence and Knowledge of Accounting and Audit partially affect the Accuracy of Giving Audit Opinion. Whereas the variable Audit Expertise and Auditor Skeptism partially do not have an influence on the accuracy of the Audit Opinion.